The Nutritive and Feeding Value of Olive Cake for Ruminants - Gürhan Keleş (Turkish Journal of Agriculture: Food Science and Technology)
The factor affecting nutritive and feeding value of olive cake (OC) was evaluated and, some suggestion was made regarding using olive cake in ruminant nutrition. It is evaluated that the nutritive value of OC can be able to support maintenance requirement of ruminant, although its nutritive value is affected by different factors. However, when taking into consideration of expense needed for preservation of OC, it is wise to use OC in nutrition after de-stoning. The crude protein, ether extract, NDF, lignin and non-fiber carbohydrates content of partly de-stoned OC (POC) was determined as 75 (56-93), 126 (68-184), 571 (443-700), 222 (174-269) and 141 (55-227) g/kg dry matter (DM). These values show that POC is a valuable source of ruminant feed. Besides, high and quality ether extract content of OC separates it from other feed and made it a special feed. Treatment with alkali increases the degradability and in vivo digestibility parameters of OC. Therefore, ensiling allowing the treatment with additives is best option to preservation of OC. Even, additional extraction of oil from POC decreases its nutritive value; studies showed that POC after additional oil extraction has still favorable nutritive value. Studies showed no adverse effect when POC substitute 20% of ration of feedlot lamb. For dairy animal, it is evaluated using POC to provide 15-20 g/kg DM oil when it substitute of 10-20% of total ration allow to produce more milk with increased fat and quality. In conclusion, de-stoning process turns OC to a valuable feed source, allows reduce feed cost, and increase animal performance and product quality. However, because nutritive value of OC affecting from very different factors, it can be propose analyze its nutritive value before using it in ruminant nutrition.